ESHRE PGT Consortium data collection XXI: PGT analyses in 2018. Issue 2 (19th April 2023) - Spinella, F; Bronet, F; Carvalho, F; Coonen, E; De Rycke, M; Rubio, C; Goossens, V; Van Montfoort, A
ABSTRACT: STUDY QUESTION: What are the trends and developments in preimplantation genetic testing (PGT) in 2018 as compared to previous years? SUMMARY ANSWER: The main trends observed in this 21st dataset on PGT are that the implementation of trophectoderm biopsy with comprehensive whole-genome testing is most often applied for PGT-A and concurrent PGT-M/SR/A, while for PGT-M and PGT-SR, single-cell testing with PCR and FISH still prevail. WHAT IS KNOWN ALREADY: Since it was established in 1997, the ESHRE PGT Consortium has been collecting and analysing data from mainly European PGT centres. To date, 20 datasets and an overview of the first 10 years of data collections have been published. STUDY DESIGN, SIZE, DURATION: The data for PGT analyses performed between 1 January 2018 and 31 December 2018 with a 2-year follow-up after analysis were provided by participating centres on a voluntary basis. Data were collected using an online platform, which is based on genetic analysis and has been in use since 2016. PARTICIPANTS/MATERIALS, SETTING, METHODS: Data on biopsy method, diagnostic technology, and clinical outcome were submitted by 44 centres. Records with analyses for more than one PGT for monogenic disorders (PGT-M) and/or PGT for chromosomal structural rearrangements (PGT-SR), or with inconsistent data regarding the PGT modality, were excluded. All transfers performed within 2 years after the analysis were included, enabling the calculation of cumulative pregnancy rates. Data analysis, calculations, and preparation of figures and tables were carried out by expert co-authors. MAIN RESULTS AND THE ROLE OF CHANCE: The current data collection from 2018 covers a total of 1388 analyses for PGT-M, 462 analyses for PGT-SR, 3003 analyses for PGT for aneuploidies (PGT-A), and 338 analyses for concurrent PGT-M/SR with PGT-A. The application of blastocyst biopsy is gradually rising for PGT-M (from 19% in 2016–2017 to 33% in 2018), is status quo for PGT-SR (from 30% in 2016–2017 to 33% in 2018) and has become the most used biopsy stage for PGT-A (from 87% in 2016–2017 to 98% in 2018) and for concurrent PGT-M/SR with PGT-A (96%). The use of comprehensive, whole-genome amplification (WGA)-based diagnostic technology showed a small decrease for PGT-M (from 15% in 2016–2017 to 12% in 2018) and for PGT-SR (from 50% in 2016–2017 to 44% in 2018). Comprehensive testing was, however, the main technology for PGT-A (from 93% in 2016–2017 to 98% in 2018). WGA-based testing was also widely used for concurrent PGT-M/SR with PGT-A, as a standalone technique (74%) or in combination with PCR or FISH (24%). Trophectoderm biopsy and comprehensive testing strategies are linked with higher diagnostic efficiencies and improved clinical outcomes per embryo transfer. LIMITATIONS, REASONS FOR CAUTION: The findings apply to the data submitted by 44 participating centres and do not represent worldwide trends in PGT. Details on the health of babies born were not provided in this manuscript. WIDER IMPLICATIONS OF THE FINDINGS: The Consortium datasets provide a valuable resource for following trends in PGT practice. STUDY FUNDING/COMPETING INTEREST(S): The study has no external funding, and all costs are covered by ESHRE. There are no competing interests declared. TRIAL REGISTRATION NUMBER: N/A.